Integrating RNA-seq and population genomics to elucidate salt tolerance mechanisms in flax (Linum usitatissimum L.) - Li, Yuan-Dong; Li, Xiao; Zhu, Lei-Lei; Yang, Yang; Guo, Dong-Liang; Xie, Li-Qiong (Frontiers in Plant Science, 2024)
Salinity is an important abiotic environmental stressor threatening agricultural productivity worldwide. Flax, an economically important crop, exhibits varying degrees of adaptability to salt stress among different cultivars. However, the specific molecular mechanisms underlying these differences in adaptation have remained unclear. The objective of this study was to identify candidate genes associated with salt tolerance in flax using RNA-Seq combined with population-level analysis.To begin with, three representative cultivars were selected from a population of 200 flax germplasm and assessed their physiological and transcriptomic responses to salt stress. The cultivar C121 exhibited superior osmoregulation, antioxidant capacity, and growth under salt stress compared to the other two cultivars. Through transcriptome sequencing, a total of 7,459 differentially expressed genes associated with salt stress were identified, which were mainly enriched in pathways related to response to toxic substances, metal ion transport, and phenylpropanoid biosynthesis. Furthermore, genotyping of the 7,459 differentially expressed genes and correlating them with the phenotypic data on survival rates under salt stress allowed the identification of 17 salt-related candidate genes.Notably, the nucleotide diversity of nine of the candidate genes was significantly higher in the oil flax subgroup than in the fiber flax subgroup. These results enhance the fundamental understanding of salt tolerance mechanisms in flax, provide a basis for a more in-depth exploration of its adaptive responses to salt stress, and facilitate the scientific selection and breeding of salt-tolerant varieties.